Consumer Preferences for Information Sources of Turfgrass Products and Lawn Care. (1st July 2017) - Yue, Chengyan; Wang, Jingjing; Watkins, Eric; Bonos, Stacy; Nelson, Kristen; Murphy, James A.; Meyer, William; Horgan, Brian
Abstract : Core Ideas: Turfgrass consumers trusted information from families, university extension, and garden centers the most. Homeowners ranked garden center/hardware stores, followed by families and then lawn care companies as the most useful information sources. Information from university extension and regional water management authorities were considered as trustworthy but less useful. Consumers need adequate information about turfgrasses attributes and lawn maintenance practices when they choose what types of turfgrasses to grow in their home lawns. We conducted online surveys with 2167 homeowners from the United States to explore what information sources they consider as trustworthy and useful regarding lawn care. We found turfgrass consumers trusted information from families, University extensions, and garden centers/hardware stores the most; these information sources were equally trusted. Whereas, they ranked garden centers/hardware stores, followed by families and then lawn care companies as the most useful information sources. Information from University extensions and regional water management authorities were considered as trustworthy but less useful. Other information sources (such as the Internet, books, manufacturer websites, and third party reviews) were considered as the least trustworthy and least useful sources. Homeowners' socio‐demographic backgrounds affected their attitude toward lawn care information sources. The results of the study have important marketing implications for turfgrass suppliers and can help guide outreach efforts by University extension educators.